การพัฒนาระบบการตรวจติดตามคุณภาพภายในของสถาบันราชภัฏ - เฉลิมชัย หาญกล้า (จุฬาลงกรณ์มหาวิทยาลัย, 2002)
To develop an internal quality audit (IQA) system for Rajabhat Institutes. Main concepts as applied in this case were 1) the system 2) system development and 3) internal quality auditing. In the descriptive research, a structured interview and a document analysis form were used to collect data from persons and documents relevant to the IQA system of Rajabhat Institutes. Descriptive statistics were used to analyse the data and obtain informations for designing the new system. The system was verified by experts and evaluated by concerned persons at Rajabhat Institutes. The research findings indicate that a suitable and feasible IQA system is composed of five components, as follows: 1. Input component: objectives, principles, quality auditors, and audit tools 2. Process component: audit preparation, audit performance, audit conclusion, measuring the effectiveness of the IQA, management review, and corrective action and follow-up 3. Output component: IQA report 4. Feedback component: the informations from measuring the effectiveness of the IQA, management review, and corrective action and follow-up 5. Environment component: environmental management.